MicroRNA profile of extracellular vesicles released by Müller glial cells - Lamb, William D. B.; Eastlake, Karen; Luis, Joshua; Sharif, Najam A.; Khaw, Peng T.; Limb, G. Astrid (Frontiers in Cellular Neuroscience, 2024)
As any other radial glia in the central nervous system, Müller glia derive from the same neuroepithelial precursors, perform similar functions and exhibit neurogenic properties as radial glia in the brain. Müller glial cells retain progenitor-like characteristics in the adult human eye, and can partially restore visual function upon intravitreal transplantation into animal models of glaucoma. Recently, it has been demonstrated that intracellular communication is possible via the secretion of nano-sized membrane-bound extracellular vesicles (EV), which contain bioactive molecules like microRNA (miRNA) and proteins that induce phenotypic changes when internalised by recipient cells. We conducted highthroughput sequencing to profile the microRNA signature of EV populations secreted by Müller glia in culture, and used bioinformatics tools to evaluate their potential role in the neuroprotective signalling attributed to these cells.Sequencing of miRNA within Müller EV suggested enrichment with species associated with stem cells such as miR-21 and miR-16, as well as with miRNA previously found to play a role in diverse Müller cell functions in the retina: miR-9, miR-125b and the let-7 family. A total of 51 miRNA were found to be differentially enriched in EV compared to whole cells from which EV originated. Bioinformatics analyses also indicated preferential enrichment of species demonstrated to regulate genes involved in cell proliferation and survival, including PTEN the master inhibitor of the PI3K/AKT pathway.The results suggest that the release by Müller cells of miRNA-enriched EV abundant in species that regulate anti-apoptotic signalling networks, is likely to represent a significant proportion of the neuroprotective effect observed after transplantation of these cells into animal models of retinal ganglion cell (RGC)-depletion. Future work will seek to evaluate the modulation of putative genes, as well as the activation of these pathways in in vitro and in vivo models following the internalisation of Müller-EV by target retinal neurons.